2021
DOI: 10.1002/qua.26779
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the enhanced performance of Sb2S3/doped‐carbon composites as potential anode materials for sodium‐ion batteries: A density functional theory approach

Abstract: The improvement of performance in sodium ion batteries is a subject of intense research. In this work, a first principle calculations study at the density functional level on the adsorption process of Na adatoms into Sb2S3/carbon (Sb2S3/CM) and Sb2S3/heteroatom doped‐carbon (Sb2S3/S‐CM, Sb2S3/Sb‐CM) is presented. The sulfur and antimony doped‐carbon substrates enhance the adsorption energies, charge transfer, specific capacities and the diffusion properties of Na adatoms into the Sb2S3/S‐CM and Sb2S3/Sb‐CM com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 43 publications
1
1
0
Order By: Relevance
“…Consequently, the lower OCV delivers a higher rate capacity and operating security. The findings of this present effort are comparable to currently reported 2D anode materials, e.g., Ti 3 C 2 (0.14 V), VSi 2 N 4 (0.16 V), 44 Sb 2 S 3 /Sb (0.18 V), 45 SiS (0.1 V), 39 and BC 3 N 3 (0.15 V), 46 which demonstrate that GeSiBi 2 monolayers are conducive to function as a low charge/discharge state prospective anode material.…”
Section: Theoretical Specific Capacity and Open Circuit Voltage (Ocv)supporting
confidence: 91%
“…Consequently, the lower OCV delivers a higher rate capacity and operating security. The findings of this present effort are comparable to currently reported 2D anode materials, e.g., Ti 3 C 2 (0.14 V), VSi 2 N 4 (0.16 V), 44 Sb 2 S 3 /Sb (0.18 V), 45 SiS (0.1 V), 39 and BC 3 N 3 (0.15 V), 46 which demonstrate that GeSiBi 2 monolayers are conducive to function as a low charge/discharge state prospective anode material.…”
Section: Theoretical Specific Capacity and Open Circuit Voltage (Ocv)supporting
confidence: 91%
“…It has been found that heteroatoms-doped graphene or carbon usually accounts for the improvement of electronic and ionic conductivity [164,165] or improve the adsorption of Sb 2 S 3 on the matrix [166,167]. Moreover, density function theory (DFT) calculation confirmed that the sulfur and Sb doped-carbon substrates increase the adsorption energies, charge transfer, specific capacities and the diffusion properties of Na + ions [168]. A similar effect can be also realized in 2D Mxene-modified chalcogenide anodes for SIB [169].…”
Section: Sb-based Chalcogenide Anodementioning
confidence: 97%